Acclimation of cadmium-induced genotoxicity and oxidative stress in mung bean seedlings by priming effect of phytohormones and proline. - Meher Hassan (Public Library of Science (PLoS), 2021)
In this research, eight local mung bean (Vigna radiata) varieties were analyzed for their performance against two levels of CdCl2 solution (0.3 and 0.5 mM) alone and priming with gibberellic acid (GA3) (100 μM), salicylic acid (SA) (50 μM) and proline (5 mM) solution prior to Cd exposure. Mung bean seedlings were analyzed for disturbance in cytological, morphological, biochemical and enzymatic parameters under cadmium stress. For cytological studies, 48 h grown mung bean seedlings root tips were used to prepare slides and studied for percent mitotic index (MI%) and to calculate percent C-mitosis, laggard, sticky and fragmented chromosomes, pictures were captured by a Nikon camera (DS-Fi 1 Japan) attached with a microscope. One-week grown mung seedlings were studied for growth traits, malondialdehyde (MDA), protein, proline and antioxidant enzymes. ANOVA and DMR test of this research revealed that all the tested mung bean varieties and treatments were significantly different regarding mitotic index and number of chromosomal aberrations. Both the Cd treatments exhibited increased total chromosomal aberrations with different types and a maximum decrease in MI%. In pretreated samples, GA3, SA and proline serve as mitigating agents that reduce mutagenic effects of Cd in mung bean by increasing MI% and decreasing chromosomal aberrations as compared to non-pretreated samples. Both the Cd treatments showed a decrease in all growth traits. Total proteins were also found to be significantly reduced in a dose-dependent manner in all genotypes. Cd treatment increased the activities of all antioxidant enzymes tested. Cd caused oxidative damage as indicated by elevated levels of MDA content in treated samples in comparison to control. Proline content levels were also high in Cd treated seedlings indicating stress. Results demonstrated that pretreatment with phytohormones and proline before Cd were found to improve all morphological parameters, by altering antioxidant enzymes activities along with a decrease in MDA and proline contents as well. It was further noticed that the performance of GA3 was better at 0.3 mM Cd treatment while SA was found to be a good mitigating agent at 0.5 mM Cd stress in all tested mung bean varieties. This research concluded less deleterious effects of Cd on AZRI-2006 while more sensitivity to NM-51 towards Cd. Priming with phytohormones and proline is a user-friendly, economical, and simple mitigation strategy to reduce Cd toxicity in plants and get better yield from contaminated lands.